PERJANJIAN PENGADAAN BARANG INFORMASI TEKNOLOGI (IT) ANTARA CV. DHYMAS COM DENGAN PT. GAPURA ANGKASA DALAM PELAKSANAANNYA - DIAN SASMITA HSB (JURNAL CIVIL LAW USU, 2013)
Abstrak : The existence of the goods/ services procurement appears as part of the development process which is included to the government’s working progress. The good procurement process of goods/ services will support the development of a country due to the right use of the government budget will support the development which is resulted the economic growth. But in practice, procurement contracts for goods/ services often have problem because it violatethe regulations. There are several bad cases of the goods/ services procurement which are found with the big financial usage. It will be resulted the state losses. Keyword: The Goods and Services Procurement, agreement